Pengaruh Locus of Control, Keefektifan Pengendalian Internal, Kesesuaian Kompensasi dan Perilaku Tidak Etis Terhadap Kecenderungan Kecurangan (FRAUD) (Studi Kasus Pada Lembaga Perkreditan Desa se-Kecamatan Buleleng): (Studi Kasus pada Lembaga Perkreditan Desa Se-Kecamatan Buleleng) - Komang Nadia Saraswati; I Gusti Ayu Purnamawati (Universitas Pendidikan Ganesha, 2022)
This research aimed to know the influence of the locus of control system, the effectiveness of internal control, the compensation suitability and the unethical behavior towards the fraud tendency at Village Credit Institutions in Buleleng District. The population in this study were all Village Credit Institution heads, Village Credit Institution secretaries, and Village Credit Institution treasurers, where the number of villages in Buleleng District were 21 villages with 51 Village Credit Institution heads, Village Credit Institution secretaries, and Village Credit Institution treasurers. So, the total number of samples used was 51 respondents. The method of data collection was done by distributing questionnaires and measured using a Likert Scale. Meanwhile, primary data testing was gained by testing data quality, classical assumption test, and hypothesis test through SPSS 24 software program. The study results indicated that the locus of control had a positive and significant effect on the fraud tendency at Village Credit Institutions in Buleleng District. The effectiveness of internal control had a negative and significant effect on the fraud tendency at Village Credit Institutions in Buleleng District. Then, the compensation suitability had a negative and significant effect on the fraud tendency at Village Credit Institutions in Buleleng District.